Diet of Poecilia reticulata Peters, 1959 in streams from Paraná River basin: influence of the urbanization (Acta Scientiarum. Biological Sciences, 2016)
This study aimed to assess the diet of Poecilia reticulata in rural (RS) and urban stream (US) and under seasonal influence. We hypothesized that rainfall have a strong negative impact on the diet of the species in the US, due to its abrupt effect on food resources; in RS this effect is less apparent. Both streams belong to Pirapó River sub-basin, Paraná River basin. Fishes were sampled bimonthly, between July 2007 and June 2008 in three sample sites along the longitudinal gradient of the streams, using electrofishing. According to the Feeding Index, in both streams the population consumed almost exclusively detritus associated with aquatic organisms (>95%), regardless of the hydrological period. The main taxa explored by fish were Simuliidae in RS and Chironomidae in US. The diet was significantly different between streams; however, the seasonal factor was not significant, showing that the results were partially consistent with the suggested proposal. In US stream the diet of the fish followed an ordinarily pattern found in urban environments. Thus, P. reticulata can be used as a tool to assess environmental conditions due to its ability to reach bioindicator organisms, such as Chironomidae species.